Preparation and characterization of urea-formaldehyde-pepsin bioconjugate: a new biocatalyst system - Vinod, V. P.; Shinde, Sudhirkumar; D'Britto, Virginia; Shukla, P. G.; Rao, Mala (Biotechnology Progress, 2006)
This study describes the synthesis of urea formaldehyde (UF) microspheres by a dispersion polycondensation polymerization method. These microspheres with proper F/U molar ratio can provide highly reactive groups, capable of further condensation with the amino acid residues of enzyme/proteins. Presence of methylols groups in UF microspheres was confirmed by C-13 NMR study. Pepsin, a proteolytic enzyme, was immobilized on the UF microspheres to form bioconjugate system. As compared to the free enzyme in solution, the pepsin in the bioconjugate system exhibited significantly enhanced pH and temperature stability. The urea-formaldehydepepsin bioconjugate system also exhibited excellent proteolytic activity over eight successive reuse cycles with more than 50% of initial activity. A highlight of this new biocatalyst is the ease with which separation of this biocatalyst from the reaction medium may be achieved by mild centrifugation.